Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1021/jacs.5b08611
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, Regioconvergent, Solvent-Free Alkene Hydrosilylation with a Cobalt Catalyst

Abstract: Alkene hydrosilylation is typically performed with Pt catalysts, but inexpensive base-metal catalysts would be preferred. We report a Co catalyst for anti-Markovnikov alkene hydrosilylation that can be used without added solvent at low temperatures with low loadings, and can be generated in situ from an air-stable precursor that is simple to synthesize from low-cost, commercially available materials. In addition, a mixture of Co catalysts performs a tandem catalytic alkene isomerization/hydrosilylation reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(94 citation statements)
references
References 38 publications
3
91
0
Order By: Relevance
“…Chen et al reported a cobalt-based catalyst for the anti-Markovnikov alkene hydrosilylation under solvent-free conditions at low temperatures and low catalyst loadings ( Figure 39) [116]. Additionally, the catalysts can be synthesized in-situ from commercially available, low-cost precursors under ambient conditions giving high yields/selectivity for functionalized alkenes (namely 1a = 89%/>98%, 1b = 94%/98%, 1c = 89%/98%).…”
Section: High Efficient/low-cost Hydrosilylation (Solvent-free Conditmentioning
confidence: 99%
“…Chen et al reported a cobalt-based catalyst for the anti-Markovnikov alkene hydrosilylation under solvent-free conditions at low temperatures and low catalyst loadings ( Figure 39) [116]. Additionally, the catalysts can be synthesized in-situ from commercially available, low-cost precursors under ambient conditions giving high yields/selectivity for functionalized alkenes (namely 1a = 89%/>98%, 1b = 94%/98%, 1c = 89%/98%).…”
Section: High Efficient/low-cost Hydrosilylation (Solvent-free Conditmentioning
confidence: 99%
“…Speier and Karstedt have demonstrated the use of platinum catalysts for direct Si‐H bond activation in hydrosilylation, and has been employed in industrial‐scale manufacturing . Intensive research in hydrosilylation have led to the discovery of other effective catalysts such as earth‐abundant Fe, Ni, and Co metals . In addition, recent advancement demonstrated the metal‐free hydrosilylation using electron‐deficient borane Lewis acid catalysts …”
Section: Hydrosilylation Via Photo‐generated Silyl Radicalsmentioning
confidence: 99%
“…The scope for the unsaturated substrate is versatile, including alkene,, , alkyne, carbonyl, and carboxylic derivative groups. Additionally, a number of different silanes can be used: much research is performed with phenylsilane, and other silanes such as diphenylsilane, alkyl silanes, and alkoxy silanes, can be employed as well.…”
Section: Introductionmentioning
confidence: 99%